Exploring the role of asexual multiplication in poplar rust epidemics: impact on diversity and genetic structure - Benoît Barrès; Cyril Dutech; Axelle Andrieux; Fabien Halkett; Pascal Frey (Molecular Ecology, 2012)
Fungal plant pathogens, especially rust fungi ( P ucciniales), are well known for their complex life cycles, which include phases of sexual and asexual reproduction. The effect of asexual multiplication on population genetic diversity has been investigated in the poplar rust fungus M elampsora larici‐populina using a nested hierarchical sampling scheme. Four hierarchical levels were considered: leaf, twig, tree and site. Both cultivated and wild poplar stands were sampled at two time points at the start and end of rust epidemics. A total of 641 fungal isolates was analysed using nine microsatellite markers. This study revealed that the genetic signature of asexual multiplication in the wild poplar stand was seen only at lower hierarchical levels (leaf and twig). Moreover, we observed an erosion of clonal structure through time, with an increase in both gene and genotypic diversity. New genotypes contributed to host infection over time, which demonstrates the importance of allo‐infection in the epidemic process in this host‐pathogen system. Compared with the wild stands, the nearly lack of detection of clonal structure in the cultivated stands reflects the higher infection level on cultivated poplars. More generally, this genetic analysis illustrates the utility of population genetics approach for elucidating the proportion of asexual reproduction in the multiplication of isolates during an epidemic, and for proper quantification of asexual dispersal in plant pathogens.